Enhanced gas-liquid mass transfer coefficient by bulk nanobubbles in water. (2022) - Sharma, Harsh; Nirmalkar, Neelkanth
Abstract: Liquid-gas operation explores the widespread applications in multiple chemical processes industries. For an instance, the inclusion of fermentation, dissolved air flotation, paper and pulp processing, sludge decomposition, aeration, ozonation, etc. are majorly covered. Liquid-gas contacting devices are primarily employed to perform their mixing, and the conventional contacting devices envelopes the fine bubble diffusers, jet aerators, surface aerators, static mixers, ejectors, etc. The gas transfer into the liquid is done by bubble formation, and the bubbles furthermore diffuses into the bulk liquid. The bubble size plays an important role in the transfer of gas, lower the size of bubbles, more is the rate of gas transfer, such as the mass transfer coefficient is remarkably enhanced by microbubbles when compared with milli-bubbles. In this work, we created O2 nanobubbles by sparging oxygen gas into nanopores, and during the production of nanobubbles, we examined the oxygen gas volumetric mass transfer coefficient (kL a) into the water. Nanoparticle tracking analysis was used to determine the population and size of nanobubbles, and we found that the population of nanobubbles is in the order of 10 7 bubbles/mL, with a mean diameter of 100–200 nm. The gassing out technique determines the volumetric mass transfer coefficient (kL a), and the influence of gas flow rate on the volumetric mass transfer coefficient (kL a) has been demonstrated to be positive. The volumetric mass transfer coefficient (kL a) in the case of nanobubbles is found significantly larger than that of microbubbles, ranging from 2.2 to 3.8 min −1 .